Method for hafnium powder production by electrolisis - Mukhachov, A.P.; Kharytonova, Е.А. (Вопросы атомной науки и техники, 2018)
Principle possibility of hafnium metal powder production by electrochemical reduction of hafnium fluorides of various compositions was investigated. Optimum content of hafnium in cathode deposit was determined. Hydrometallurgical processing of cathode deposit using a 10% potassium carbonate solution demonstrated 95% efficiency of hafnium powder extraction. Electrolysis of hafnium fluoride salts in an open-type electrolysis does not make it possible to obtain hafnium metal powder with a low content of interstitial gas impurities and requires iodide refining to remove oxygen and nitrogen. Best process-oriented results were obtained by electrolysis of HfF₄-KCl-KF-system. Вивчена принципова можливість отримання порошку металевого гафнію методом електрохімічного відновлення фторидів гафнію різного складу. Визначено оптимальний зміст гафнію в катодному осаді. Гідрометалургійна переробка катодного осаду із застосуванням 10% розчину поташу показала ефективність вилучення порошку гафнію зі ступенем 95%. Відкритий електроліз фторидних солей гафнію не дозволяє отримати порошок металевого гафнію з низьким змістом газових домішок впровадження, порошок вимагає йодидне рафінування для очищення від кисню та азоту. Найкращі технологічні результати отримані при електролізі системи HfF₄-KCl-KF. Изучена принципиальная возможность получения порошка металлического гафния методом электрохимического восстановления фторидов гафния различного состава. Определено оптимальное содержание гафния в катодном осадке. Гидрометаллургическая переработка катодного осадка с применением 10% раствора поташа показала эффективность извлечения порошка гафния со степенью 95%.Открытый электролиз фторидных солей гафния не позволяет получить порошок металлического гафния с низким содержанием газовых примесей внедрения, порошок требует йодидного рафинирования для очистки от кислорода и азота. Наилучшие технологические результаты получены при электролизе системы HfF₄-KCl-KF.